ChemInform Abstract: Synthesis and Stability of Boratriazaroles. Issue 21 (May 2015) - Zurwerra, Didier; Quetglas, Vincent; Kloer, Daniel P.; Renold, Peter; Pitterna, Thomas
Abstract The condensation reaction of amidrazone and different arylboronic acids to gain access to boratriazaroles is reported.